مفهوم الأهلية في قانون العقوبات العراقي - كريم سلمان كاظم التميمي (Journal of Madenat Alelem University College, 2015)
The murder relates with crime by two relationships: physical relationship is a causal relationship between criminal behavior and criminal result, moral and civil relationship is punitive. The Penal Code in the early stages of its inception, is heading to the sufficiency of material Association. The first consideration go out towards the result caused by the criminal behavior of the offender, regardless of his will in the events of the act or the result. As a result of the evolution of the Penal Code Not only in the crime and responsibility as soon as the material element where required to the terms of his character is the most important of these conditions eligibility Civil elements are not only the conditions that law requires invoked by the will of the perpetrator and is the perception and the will, and assume that the elements of civil criminally charge any natural person (man). He alone has the cognitive abilities and the will, as you go to the most contemporary criminal laws, which require explicitly the need for cognition and the will ((ie civil)) to check criminal responsibility. One of these laws, the Iraqi Penal Code, where Article (60) than on it (do not ask criminally from the time of the offense, or unconscious cognition will